Implementation strategies to increase seasonal influenza vaccination among adults: A rapid scoping review - Katherine Adams; Joanna Taliano; Ijeoma Okorie; Melissa Alvendia; Palak Patel; Shikha Garg; Larry W. Chang (Human Vaccines & Immunotherapeutics)
Many strategies have been applied to increase seasonal influenza vaccination; however, gaps in coverage remain. We synthesized the evidence on effectiveness of implementation strategies to increase seasonal influenza vaccination among U.S. adults. Studies performed from February 2010–August 2023 in the United States, focused on seasonal influenza vaccination, and measuring uptake and coverage were included. Guidance from Cochrane was followed. Interventions were mapped to Expert Recommendations for Implementing Change strategies. A total of 1,585 non-duplicate records were identified, full-text screening was performed for 353 records, and 51 studies met inclusion criteria. Among these studies, implementation strategies included those that engaged consumers, trained and educated stakeholders, and supported providers. Considerable heterogeneity was found in the study setting, populations, design, and methods. Substantial study variation limits the ability to conclude which strategies are most effective at increasing influenza vaccination uptake and coverage in U.S. adults.